2013
DOI: 10.1245/s10434-012-2858-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Metachronous Colon Cancer Following Surgery for Rectal Cancer in Mismatch Repair Gene Mutation Carriers

Abstract: Background Despite regular surveillance colonoscopy, the metachronous colorectal cancer risk for mismatch repair (MMR) gene mutation carriers after segmental resection for colon cancer is high and total or subtotal colectomy is the preferred option. However, if the index cancer is in the rectum, management decisions are complicated by considerations of impaired bowel function. We aimed to estimate the risk of metachronous colon cancer for MMR gene mutation carriers who underwent a proctectomy for index rectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 18 publications
1
79
1
1
Order By: Relevance
“…Best oncologic outcome is balanced by competing risks from extra colonic cancers and metachronous disease with preservation of sphincter function and quality of life issues (Coffey et al, 2002;Wertzberger et al, 2014). The risk of metachronous colon cancer has been reported as 19% at 10 years (Cirillo et al, 2013;Kalady et al, 2012;Lee et al, 2001;Win et al, 2013) with an up to a six-fold increase in mortality risk if a metachronous cancer develops (Cirillo et al, 2013). Thus, an aggressive approach is warranted in disease recurrence and/or metachronous CRC.…”
Section: Rectal Cancer With Msimentioning
confidence: 99%
“…Best oncologic outcome is balanced by competing risks from extra colonic cancers and metachronous disease with preservation of sphincter function and quality of life issues (Coffey et al, 2002;Wertzberger et al, 2014). The risk of metachronous colon cancer has been reported as 19% at 10 years (Cirillo et al, 2013;Kalady et al, 2012;Lee et al, 2001;Win et al, 2013) with an up to a six-fold increase in mortality risk if a metachronous cancer develops (Cirillo et al, 2013). Thus, an aggressive approach is warranted in disease recurrence and/or metachronous CRC.…”
Section: Rectal Cancer With Msimentioning
confidence: 99%
“…DNA base substitutions, insertions and deletions in these regions result in dysregulation of the cell cycle and ultimately lead to carcinogenesis. MSI can also be caused by de novo hypermethylation of MLH1 gene promoter and is seen in 20% of sporadic cancer (25). Screening for MSI or DNA mismatch repair is the first step to diagnosis.…”
Section: Genetic Basis For Diagnosismentioning
confidence: 99%
“…However, the risk of metachronous colorectal cancer with partial colectomy is eliminated if a subtotal colectomy is performed (30,31). Furthermore, younger patients may benefit from total proctocolectomy and ileal pouch anal anastomosis given the increased occurrence of metachronous colorectal cancer with age (25). Although segmental colectomy with adequate surveillance remains an option it should typically be reserved for elderly patients or those that cannot tolerate a subtotal colectomy due to the increased lifetime risk of developing a metachronous colorectal cancer.…”
Section: Genetic Basis For Treatmentmentioning
confidence: 99%
“…When considering the surgical strategy for CRC patients with Lynch syndrome, the rate of developing metachronous CRC according to the different surgeries is an important consideration. Several reports showed that the 6- to 10-year cumulative risk of metachronous CRC was 15.7–25% in patients undergoing SGC and 0–8% in patients undergoing STC [8-10, 23-25]. A recent meta-analysis evaluated the difference in the risk of developing metachronous CRC between the 2 surgical procedures and concluded that the incidence of metachronous CRC was significantly higher after SGC than after STC (OR 3.679, p < 0.005) [26].…”
Section: Discussionmentioning
confidence: 99%